Help me again, please. ;w;
![Help me again please w class=](https://us-static.z-dn.net/files/dde/2f3dae0e1132be14e2721fbdfee8011e.png)
5x - 7y =58
y =-x +2
Using the substitution method, replace y in the first equation with the second equation:
5x - 7(-x+2) = 58
Simplify by using the distribution property:
5x - (-7x) - 14 = 58
Simplify by combining like terms:
12x -14 = 58
Add 14 from each side of the equation:
12x = 72
Divide both sides by 12:
X = 72/12
x = 6
Now you have x, replace x in the second equation and solve for y:
y = -x +2
y = -6 +2
y = -4
X = 6, y = -4